2017
DOI: 10.4028/www.scientific.net/kem.753.300
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Performance of Compound Improved HLLS (High Liquid Limit Soil) with Various Curing Agents

Abstract: The HLLS (high liquid limit soil) has the characteristics of high moisture content, low bearing capacity and poor water stability. Most of the existing treatment methods focus on the improvement with a single curing agent, and the research on the improvement of HLLS with various curing agents is still insufficient. This paper presents the characteristics of two kinds of compound improved HLLS based on unconfined compressive strength test. The results show that the unconfined compressive strength of CSIS (Cemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…As the curing age increased, the q u and E gradually increased; in the actual construction process, the strength growth ratio from 7 to 28 days is an important guarantee for the project's continuously stable and efficient progress. Assuming the G represents the growth ratio of the q u and E from the 7th curing day to the 28th curing day, the growth ratio of q u and E can be calculated using Equations ( 1) and (2). When the proportion of the inorganic material was 15%, G qumax = 32.98% and G Emax = 20.94%.…”
Section: E=1922mpamentioning
confidence: 99%
See 1 more Smart Citation
“…As the curing age increased, the q u and E gradually increased; in the actual construction process, the strength growth ratio from 7 to 28 days is an important guarantee for the project's continuously stable and efficient progress. Assuming the G represents the growth ratio of the q u and E from the 7th curing day to the 28th curing day, the growth ratio of q u and E can be calculated using Equations ( 1) and (2). When the proportion of the inorganic material was 15%, G qumax = 32.98% and G Emax = 20.94%.…”
Section: E=1922mpamentioning
confidence: 99%
“…High-liquid-limit soil refers to fine-grained soil with a liquid limit greater than 50% and a plasticity index greater than 26 [1], which is widely distributed in the Chinese southern where the rainfall and lake are abundant. Due to the high water content, low strength, and poor water stability, it cannot be directly applied to subgrade filling [2] and may cause severe diseases such as roadbed cracking, uneven settlement and slope instability [3]. Aiming to dispose the high liquid limit soil, there are mainly two types of the method proposed by researchers [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Few authors who have investigated the liquid polymer-based product (Renolith) concluded that it has significantly improved the workability of the cement stabilization process in a variety of road subgrade, rail, embankment, and other construction projects [12]. It also improves the properties of poor soils [13]. Therefore, an experimental investigation was also carried out to ascertain its effect on a concrete mix.…”
Section: Polymer Based Additivementioning
confidence: 99%
“…The test showed that the micropores of the active MgO carbonation solidified soil significantly reduced, leading to slightly lower strength. Que [ 24 ] compared the effects of cement, lime, EN-1, and other curing agents on soil reinforcement of Fujian high-liquid-limit clay through mechanical property analysis, durability tests, microscopic tests, and numerical calculation. The results showed that the improvement effect of the ionic curing agent and polymer curing agent was obvious.…”
Section: Introductionmentioning
confidence: 99%